Увага до звукоутворення й звуковедення в роботі над удоскоаленням вокальної техніки - Карпов, В.В. (Культура народов Причерноморья, 2014)
Стаття присвячена актуальним проблемам музичної педагогіки, пов’язаним з опануванням секретів вокального мовлення, з врахуванням його специфіки в порівнянні з мовленням сценічним, а тим більше повсякденним. Звертається увага на особливу роль звукоутворення й звуковедення у вдосконаленні вокальної техніки, у належному розкритті сценічного образу. Належне опанування різними способами звукоутворення й звуковедення має безпосередній стосунок до виразності вокального виконання. Без досягнення вільного й невимушеного звукоутворення й звуковедення немислима підготовка професійного вокаліста. Статья посвящена актуальным проблемам музыкальной педагогики, связанным с постижением секретов вокальной речи, с учетом ее специфики в сравнении с речью сценической, а тем более обыденной. Обращается внимание на особую роль звукоизвлечения и зввуковедения в усовершенствовании вокальной техники, в глубоком раскрытии сценического образа. Надлежащее овладение разными способами звукоизвлечения и зввуковедения имеет непосредственное отношение к выразительности вокального исполнения. Без достижения свободного и непринужденного звукоизвлечения и зввуковедения немыслима подготовка профессионального вокалиста. The article is devoted to the actual problems of the musical pedagogic connected with the comprehension of the secrets of vocal pronunciation, with paying attention on its peculiarity in comparison with scene and everyday pronunciation. The author of this investigation takes notice to creation and direction of sound as very important aspect of a sinning technique. A correct possession of creation and direction of sound beyond an importance of other components of singing plays here a special role and therefore it is closely connected with the expressiveness of the vocal performance. The process of preparation of a professional vocalist is impossible without an educating of correct creation and direction of sound, without a possessing of a special habit in this meaning. The author of the article leans upon the works by V.A. Bagadurov, B.O. Bazilikut, L.V. Dmitriyev, U.Y. Yutsevich and other researches and musical pedagogues. But he previously uses here his own experience as the professor in Crimean University of Culture, Art and Tourism (Simferopol), in Crimean Humanitarian University (Yalta) as well as the leading actor and singer in Crimean Academic Ukrainian Musical Theatre.